Da luta pela terra à luta pela escola no e do campo: conquistas e desafios na escola Tiradentes - Carneiro, Maria Betania Neres (2024)
The following work seeks to understand how the fight for land and schooling takes place in rural environments, focusing on the development of pedagogical proposals dedicated to the children of farmers granted land by the land reform. Our subjects were the preschool teachers of the Tiradentes Settlement School. During our investigation, we dove deeply into the history of the struggles for land and schooling in rural areas, recognizing those as two dimensions of a single fight: the one for a school pedagogically associated with Rural Education principles and practices. From this problem a few questions arise: how did the struggle for land and rural schooling take place? What are the pedagogical strategies employed by the educators to reconcile the official curriculum with the principles of Rural Education and Preschool Education directive? What are the difficulties and challenges faced by these educators? To research these problems and develop the knowledge about this theme contributes to the development of Rural Education proposals for Preschool. In order to face this problem we defined as our main goal to analyze the struggles for land and rural schools in the Tiradentes School. Our specific goals include: to examine if and how the design of the educational system’s curriculum relates to the students’ reality, to identify the feasibility of Rural Education practices on preschool education and the factors that interfere with the execution of pedagogical practices. Our qualitative methodology employed the data gathering techniques of semi structured interviews (with four teachers) and documental analyses of both Rural Education policies and the school’s Political Pedagogical Project. The results indicate that the struggle for land is inseparable from the fight for rural education. The local land disputes lasted one year, taking place in Gendiroba Farm (located in Mari county) and culminating in the foundation of the settlement. The fight for a local school, however, took another 12 years - even though the settlement was founded in 1999, construction of the school building was finished only in 2012. Meanwhile, a social movement emerged in the region, dedicated to composing an educational project aligned with Rural Education principles (thus establishing a truly rural school).